MeerKAT radio detection of the Galactic black hole candidate Swift J1842.5−1124 during its 2020 outburst. Issue 1 (2nd December 2021) - Zhang, X; Yu, W; Motta, S E; Fender, R; Woudt, P; Miller-Jones, J C A; Sivakoff, G R
ABSTRACT: Swift J1842.5−1124 is a transient Galactic black hole X-ray binary candidate, which underwent a new outburst in 2020 May. We performed multi-epoch MeerKAT radio observations under the ThunderKAT large survey programme, coordinated with quasi-simultaneous Swift/XRT X-ray observations during the outburst, which lasted nearly a month. We were able to make the first-ever radio detection of this black hole binary with the highest flux density of 229 ± 31 μ Jy when the source was in the hard state, after non-detection in the radio band in the soft state which occurred immediately after its emergence during the new X-ray outburst. Therefore, its radio and X-ray properties are consistent with the disc-jet coupling picture established in other black hole X-ray binaries. We place the source's quasi-simultaneous X-ray and radio measurements on the radio/X-ray luminosity correlation plane; two quasi-simultaneous radio/X-ray measurements separated by 11 d were obtained, which span ∼2 dex in the X-ray luminosity. If the source follows the black hole track in the radio/X-ray correlation plane during the outburst, it would lie at a distance beyond ∼5 kpc.